2011
DOI: 10.1590/s1808-86942011000500019
|View full text |Cite
|
Sign up to set email alerts
|

Balance in Parkinson's disease patients changing the visual input

Abstract: The description of the postural responses in Parkinson's disease patients when visual information changes from a stable to a moving visual field analyzing the impact on balance in these patients. Methods (Clinical):Limits of Stability, Body center of pressure and balance functional reserve were measured by means of the force platform in 24 Parkinson´s patients in stages 1 and 2 of the Boher classification and 19 volunteers as a control group. Both groups were stimulated with 1-Static visual field and 2-horizon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 11 publications
(17 reference statements)
1
23
1
2
Order By: Relevance
“…However, it should be noted that these results may be related to those observed in the mCTSIB test where changes of the CoP alignment are associated with forward displacement as the disease severity progresses. As in our study, Suarez [32] observed also a decrease in the limits of stability of early stages when compared with a control group. Jessop et al [33] observed also a decrease of the maximum excursion amplitude of the CoP displacement in individuals with mild to moderate PD stages, when compared to a control group.…”
Section: ) Rws Testsupporting
confidence: 88%
“…However, it should be noted that these results may be related to those observed in the mCTSIB test where changes of the CoP alignment are associated with forward displacement as the disease severity progresses. As in our study, Suarez [32] observed also a decrease in the limits of stability of early stages when compared with a control group. Jessop et al [33] observed also a decrease of the maximum excursion amplitude of the CoP displacement in individuals with mild to moderate PD stages, when compared to a control group.…”
Section: ) Rws Testsupporting
confidence: 88%
“…In regards to balance, VR provides an avenue to implement many of the therapy strategies that have been established for physical and neurological recovery, including repetitive practice, self-observation, biofeedback and imitation of others movements. [35] An extensive evidence base has been established demonstrating the positive effects of utilizing VR for the treatment of balance deficits in neurologically similar patients, including stroke, [81][82][83][84][85][86][87][88][89][90][91][92] Parkinson's disease [80,93,94] and spinal cord injury. [35,36,95,96] Studies of varying levels of complexities in these populations have shown that groups utilizing VR have improved gait speed, standing endurance, and score higher than groups receiving the 'standard of care' on measures of posture, standing and higher level balance.…”
Section: Emerging Techniques For Balance Treatments: Virtual Realitymentioning
confidence: 99%
“…Balance disorders in individuals with Parkinson's disease (PD) can occur at different stages of the disease, increasing their physical disability 1 . This can be justified by the impairment of the central nervous system's ability to process vestibular, visual, and proprioceptive afferences, which normally interprets them to generate the appropriate muscle responses that are responsible for the maintenance of body balance 2,3 .…”
Section: Introductionmentioning
confidence: 99%